1999
DOI: 10.1590/s0034-71081999000300011
|View full text |Cite
|
Sign up to set email alerts
|

Tamanho corporal em populações naturais de Didelphis (Mammalia: Marsupialia) do Sul do Brasil

Abstract: Body size in natural populations of Didelphis (Mammalia:Marsupialia) from southern BrazilNowaday, data about marsupial biometry are poorly available in Brazil, considering the high richness of marsupial species in this country. Then, relationships of body size and sexual dimorfism of natural populations of the white-eared opossum, Didelphis albiventris, and of the common opossum, D. marsupialis, were studied in two mixed forests of Curitiba, southern Brazil, between February 1995 and February 1997. As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
3
9
0
8
Order By: Relevance
“…Some authors have reported no sexual dimorphism for Didelphis (Monteiro-Filho, 1987;Stallings, 1989), but it is common to find that at least some of the body measurements are larger in males than in females (e.g., Gardner, 1973;Tyndale-Biscoe and Mackenzie, 1976;Fonseca and Kierluff, 1989;Cherem et al, 1996;Catzeflis et al, 1997;Cáceres and Monteiro-Filho, 1999;Cerqueira and Lemos, 2000) as observed in this study. However, a variation in this pattern, such as the tail length of females from Arvoredo Island being longer than that of males, can occasionally occur.…”
Section: Measurementsupporting
confidence: 58%
See 1 more Smart Citation
“…Some authors have reported no sexual dimorphism for Didelphis (Monteiro-Filho, 1987;Stallings, 1989), but it is common to find that at least some of the body measurements are larger in males than in females (e.g., Gardner, 1973;Tyndale-Biscoe and Mackenzie, 1976;Fonseca and Kierluff, 1989;Cherem et al, 1996;Catzeflis et al, 1997;Cáceres and Monteiro-Filho, 1999;Cerqueira and Lemos, 2000) as observed in this study. However, a variation in this pattern, such as the tail length of females from Arvoredo Island being longer than that of males, can occasionally occur.…”
Section: Measurementsupporting
confidence: 58%
“…They also play a major Nevertheless, biometric information on Didelphis is restricted to general studies (e.g., Gardner, 1973;Tyndale-Biscoe and Mackenzie, 1976;Fonseca and Kierluff, 1989;Catzeflis et al, 1997;Cerqueira and Lemos, 2000) with little data being available on insular species (Cherem et al, 1996) or comparisons between populations (Cáceres and Monteiro-Filho, 1999). Even so, the few studies which have compared body size among Didelphis populations have contributed to some ecological understanding of this genus (Cáceres and Monteiro-Filho, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A dieta onívora é corroborada também pelo comprimento similar de todos os segmentos do trato digestivo (Caceres 2005). Pode ser considerada dispersora de sementes, importante na manutenção da regeneração da floresta (Caceres e Monteiro-Filho 2007), pois grande parte das sementes é viável após consumo (Caceres e Monteiro-Filho 1999).…”
Section: Dietaunclassified
“…: Caceres et al 2002, Grelle 2003, Almeida 2008) e em diversos fragmentos florestais (Caceres e Monteiro-Filho 1999, Barros 2006, Medina 2007, Guedes 2008, Pinto et al 2009), e no Rio de Janeiro como no Planalto de São Paulo, foi mais comum em fragmentos de mata do que em floresta contínua ). Apesar de ter sido raramente capturada em áreas abertas , movimenta-se entre fragmentos de mata através de áreas abertas (Pires e Fernandez 1999, Quental et al 2001, Goulart et al 2006), a distâncias de até 800 m (Pires et al 2002).…”
Section: Caracterização Do Uso De Habitats No Planalto Atlântico De Sunclassified
See 1 more Smart Citation